The Complex Co-infections of Multiple Porcine Diarrhea Viruses in Local Area Based on the Luminex xTAG Multiplex Detection Method - Shi, Ying; Li, Benqiang; Tao, Jie; Cheng, Jinghua; Liu, Huili (Frontiers in Veterinary Science, 2021)
The large-scale outbreaks of severe diarrhea caused by viruses have occurred in pigs since 2010, resulting in great damage to the pig industry. However, multiple infections have contributed to the outbreak of the disease and also resulted in great difficulties in diagnosis and control of the disease. Thus, a Luminex xTAG multiplex detection method, which was more sensitive and specific than general multiplex PCR method, was developed for the detection of 11 viral diarrhea pathogens, including PKoV, PAstV, PEDV, PSaV, PSV, PTV, PDCoV, TGEV, BVDV, PoRV and PToV. To investigate the prevalence of diarrhea-associated viruses responsible for the outbreaks, a total of 753 porcine stool specimens collected from 9 pig farms in Shanghai during 2015-2018 were tested and the pathogen spectrums and co-infections were analyzed. As a result, PKoV, PAstV and PEDV were most commonly detected viruses in diarrheal pigs with the rate of 38.65% (291/753), 20.32% (153/753), and 15.54% (117/753), respectively. Furthermore, multiple infections were commonly seen, with positive rate of 28.42%. Infection pattern of the viral diarrhea pathogens in a specific farm was changing, and different farms had the various diarrhea infection patterns. A longitudinal investigation showed that PEDV was the key pathogen which was closely related to the death of diarrhea piglets. Other pathogens might play synergistic roles in the pathogenesis of diarrhea disease. Here we provided a Luminex xTAG multiple method to detect 11 kinds of porcine viral diarrhea pathogens simultaneously. Furthermore, the surveillance confirmed that variant enteropathogenic viruses were leading etiologic agents of porcine diarrhea, either mono-infection or co-infections of PKoV were common in pigs in Shanghai, but PEDV was still the key pathogen and multiple pathogens synergistically complicated the infection status, suggesting that controlling porcine diarrhea might be more complex than previously thought. The study provides a better understanding of diarrhea viruses in piglets, which will aid in better preventing and controlling epidemics of viral porcine diarrhea.